Forståelsen af begreberne skæbne og fri vilje i moderne vestlig astrologi - Krogsdal, Iben Egekvist (Religionsvidenskabeligt Tidsskrift, 1999)
"Destiny, Free Will and Astrology". The relation between destiny and free will has, since Augustine, been crucial in the theological and philosophical approach to astrology and has led to the accusation that astrology represents pure fatalism. This article concentrates on two mainstreams in modern, Western astrology; esoteric astrology and humanistic astrology. The two different astrological schools solve the conflict between destiny and free will differently, yet stand together in rejecting the accusation of pure fatalism: Astrology is only fatalistic to the primitive unspiritual being. On higher levels of human development, will is introduced. The esoteric astrology claims that the ultimate aim of human existence through continuing incarnations is to become one with the divine. The Jungian inspired humanistic astrology emphasizes the capability of the inviduating individual to fill a structural emptiness set out be the horoscope. This is not achieved by becoming one with the divine, but by becoming one with oneself.